Blockchain For Babies - Ferrie, Chris; Tomamichel, Marco (Naperville : Sourcebooks Explore, 2019)
"Set the children in your life on a lifelong path to learning with the next installment of the Baby University board book series. Full of scientific information from notable experts, this is the perfect book to teach complex concepts in a simple, engaging way. Blockchain for Babies is a colorfully simple introduction to the technology behind Bitcoin for cryptologists of all ages. It's never too early to become a scientist!"--.
new kids book 2024 fall.
Ages 0-3.
Grades K-1.
Keywords: Blockchains (Databases) -- Juvenile literature; Cryptocurrencies -- Juvenile literature